TINGKAT KESIAPAN GURU DALAM PELAKSANAAN PEMBELAJARAN BERDIFERENSIASI PADA KURIKULUM MERDEKA DI SEKOLAH DASAR SE-KECAMATAN KEMIRI - FATINA NISA NASTITI PUTRI; Riawan Yudi Purwoko; Suyoto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the level of readiness of elementary school teachers in planning, implementing, and evaluating differentiated learning. This type of research is quantitative research with a survey approach, where the data collection technique uses a questionnaire, which will then be analyzed descriptively. The results of the study show that the mean value of the indicator for mapping students' learning needs in the learning planning section is 3.51 (High), meaning that teachers have a good understanding of differentiated learning planning. The indicator for the learning implementation process is in the "Sufficient" category with a mean value of 3.29, meaning that teachers are quite ready to implement differentiated learning even though the implementation experiences several obstacles. Meanwhile, the learning evaluation indicator is in the "High" category with a mean value of 3.64, meaning that teachers have a good understanding of strategies in evaluating differentiated learning. Based on these three indicators, it is known that the level of teacher readiness in differentiated learning is in the "High" category with an average value of 3.48, meaning that a teacher has a good understanding of the concept, strategy, and application of differentiated learning in elementary school. These findings indicate that the majority of elementary school teachers in Kemiri District understand the application of differentiated learning, but there is still a need for increased training, resources, and policy support within the school.